Assessment of sympathetic reinnervation after cardiac transplantation using hybrid cardiac PET/MRI: A pilot study. Issue 4 (20th March 2019) - Beitzke, Dietrich; Wielandner, Alice; Wollenweber, Tim; Vraka, Chrysoula; Pichler, Verena; Uyanik‐Uenal, Keziban; Zuckermann, Andreas; Greiser, Andreas; Hacker, Marcus; Loewe, Christian
Abstract : Background: Sympathetic reinnervation after heart transplantation (HTX) is a known phenomenon, which has an impact on patient heart rate variability and exercise capacity. The impact of reinnervation on myocardial structure has not been evaluated yet. Propose: To evaluate the feasibility of simultaneous imaging of cardiac reinnervation and cardiac structure using a hybrid PET/MRI system. Study type: Prospective / pilot study. Subjects: Ten patients, 4–21 years after cardiac transplantation. Field Strength/Sequence: 3 T hybrid PET/MRI system. Cine SSFP, T1 mapping (modified Look–Locker inversion recovery sequence) pre/postcontrast as well as dynamic [ 11 C]meta‐hydroxyephedrine ([ 11 C]mHED) PET. Assessment: All MRI and PET parameters were evaluated by experienced readers using dedicated postprocessing software packages for cardiac MRI and PET. For all parameters a 16‐segment model for the left ventricle was applied. Statistical Tests: Mann–Whitney U ‐test; Spearman correlations. Results: Thirty‐six of 160 myocardial segments showed evidence of reinnervation by PET. On a segment‐based analysis, mean native T1 relaxation times were nonsignificantly altered in segments with evidence of reinnervation (1305 ± 151 msec vs. 1270 ± 112 msec; P  = 0.1), whereas mean extracellular volume (ECV) was significantly higher in segments with evidence of reinnervation (35.8 ± 11% vs. 30.9 ± 7%; P  = 0.019). There were no significant differences in wall motion (WM) and wall thickening (WT) between segments with or without reinnervation (mean WM: 7.6 ± 4 mm vs. group B: 9.3 ± 7 mm [ P  = 0.13]; WT: 79 ± 63% vs. 94 ± 74% [ P  = 0.27]) under resting conditions. Data Conclusion: The assessment of cardiac reinnervation using a hybrid PET/MRI system is feasible. Segments with evidence of reinnervation by PET showed nonsignificantly higher T1 relaxation times and a significantly higher ECV, suggesting a higher percentage of diffuse fibrosis in these segments, without impairment of rest WM and WT. Level of Evidence: 3 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2019;50:1326–1335.